THE INFLUENCE OF STUDENTS’ MINDSETS ON ENGLISH SCORES DURING ENGLISH LEARNING PROCESS - rosiska, Rosiska; Priajana, Nana; Nashruddin, Wakhid (Universitas Bunda Mulia, 2024)
ABSTRACTMindset plays an important role in the teaching and learning process, which can affect student thinking, student reactions, activities, and personality. Understanding the student mindsets can increase to their teaching and learning process to be more effective and give them a positive effect and improve their English scores. The analysis was conducted to investigate the influences student mindsets on English scores during learning English process in one of Junior High School in Cirebon Regency. The study used a quantitative method with questionnaire and test [1] as data-gathering techniques. The population is eighth grade students in one of the junior high schools in Cirebon. The results of this study focused on the type of mindset that students have during the process of learning English and the results of their English scores. It showed that there is the effect between students’ mindsets and English scores as much as 74.9%. The existence of different learning styles in students contribute to this study. Improving the type of mindsets of students during English learning allows in improving English scores or academic achievement as well as the quality of English language skills more broadly than just looking at student learning outcomes. Educational institutions should take these findings into account and improve the English learning and teaching process accordingly.